Effect of Rotator Cuff Deficiencies on Muscle Forces and Glenohumeral Contact Force After Anatomic Total Shoulder Arthroplasty Using Musculoskeletal Multibody Dynamics Simulation - Chen, Zhenxian; Fan, Xunjian; Gao, Yongchang; Zhang, Jing; Guo, Lei; Chen, Shibin; Jin, Zhongmin (Frontiers in Bioengineering and Biotechnology, 2021)
Anatomic total shoulder arthroplasty (ATSA) is widely used to treat the diseases of the glenohumeral joint. However, the incidence of rotator cuff tears after ATSA increases during follow up. The effects of rotator cuff deficiencies after ATSA on the biomechanics of the glenohumeral joint are to be investigated. In this study, a musculoskeletal multibody dynamics model of ATSA was established using a force-dependent kinematics method. The biomechanical effects were predicted during arm abduction under different rotator cuff deficiencies. The deltoid forces were increased under the rotator cuff deficiencies, the maximum deltoid forces were increased by 36 % under the subscapularis deficiency and by 53 % under the supraspinatus, infraspinatus, subscapularis and teres minor deficiencies. The maximum glenohumeral contact forces were decreased by 11.3 % under supraspinatus and infraspinatus deficiencies but increased by 24.8 % under subscapularis deficiency. The maximum subscapularis force was decreased by 17 % under only infraspinatus tear during arm abduction. The results suggested that the changes in biomechanics of the glenohumeral joint induced by rotator cuff deficiencies after ATSA increase the deltoid muscle energy expenditure and joint instability, which result in postoperative less satisfactory clinical outcomes. The changes in rotator cuff muscle forces deserve more attention for understanding the evolution of rotator cuff tear after ATSA.